Room Temperature Uniaxial Magnetic Anisotropy Induced By Fe‐Islands in the InSe Semiconductor Van Der Waals Crystal. Issue 7 (11th May 2018) - Moro, Fabrizio; Bhuiyan, Mahabub A.; Kudrynskyi, Zakhar R.; Puttock, Robert; Kazakova, Olga; Makarovsky, Oleg; Fay, Michael W.; Parmenter, Christopher; Kovalyuk, Zakhar D.; Fielding, Alistar J.; Kern, Michal; van Slageren, Joris; et al.
Abstract: The controlled manipulation of the spin and charge of electrons in a semiconductor has the potential to create new routes to digital electronics beyond Moore's law, spintronics, and quantum detection and imaging for sensing applications. These technologies require a shift from traditional semiconducting and magnetic nanostructured materials. Here, a new material system is reported, which comprises the InSe semiconductor van der Waals crystal that embeds ferromagnetic Fe‐islands. In contrast to many traditional semiconductors, the electronic properties of InSe are largely preserved after the incorporation of Fe. Also, this system exhibits ferromagnetic resonances and a large uniaxial magnetic anisotropy at room temperature, offering opportunities for the development of functional devices that integrate magnetic and semiconducting properties within the same material system. Abstract : A hybrid material comprising the semiconductor van der Waals crystal InSe and ferromagnetic Fe‐islands is reported. This system exhibits ferromagnetic resonances and a large magnetic anisotropy at room temperature offering prospects for the generation of spin currents in InSe via the inverse spin Hall effect and its control by the magnetic anisotropy of the Fe‐islands.